Continuity and Preference of Ride-Sharing Service in Bangladesh: A Cul-tural Analysis - Anwar, Samiha; Halder, Arko (Future Science / FSH-PH Publications, 2025)
This study investigates the proliferation of app-based ride-hailing services within the urban transportation systems of Bangladesh, with a particular focus on socio-cultural assimilation and growing prominence. The primary objective of this research is to analyze the current dynamics of ride-sharing services in Dhaka and Chattogram, identifying the underlying factors that have contributed to their widespread adoption. It is done by qualitative data from interviews with 20 regular users in Dhaka and Chattogram. Empirical findings reveal that the preference for such services is predominantly driven by considerations of comfort, perceived safety, user convenience, and the potential for supplementary income. The analysis is done within the theoretical paradigm, employing Jan Nederveen Pieterse’s theory of Globalization as Hybridization, John Storey’s discourse on Popular Culture, and Frederic Jameson’s critique of Consumerism. Through this lens, the research demonstrates that while the concept of ride-sharing is rooted in Western socio-economic contexts, its localization in Bangladesh has led to the emergence of a hybridized cultural practice. Moreover, the study reveals that ride-sharing services have transcended their functional role, evolving into a significant facet of contemporary popular culture within urban Bangladesh. This transformation is further illustrated through the theoretical construct of consumerism, which elucidates the appeal of such services to the modern urban middle class. The paper not only underscores the cultural and economic factors contributing to the rise of ride-sharing platforms but also offers recommendations for their sustainable development and potential future expansion within the Bangladeshi context.